Synthesis, Fungicidal Activity and Mode of Action of 4-Phenyl-6-trifluoromethyl-2-aminopyrimidines against Botrytis cinerea - Chunhui Liu; Zining Cui; Xiaojing Yan; Zhiqiu Qi; Mingshan Ji; Xinghai Li (Molecules, 2016)
Anilinopyrimidines are the main chemical agents for management of Botrytis cinerea. However, the drug resistance in fungi against this kind of compounds is very serious. To explore new potential fungicides against B. cinerea, a series of 4-phenyl-6-trifluoromethyl-2-amino-pyrimidine compounds (compounds III-1 to III-22) were synthesized, and their structures were confirmed by 1H-NMR, IR and MS. Most of these compounds possessed excellent fungicidal activity. The compounds III-3 and III-13 showed higher fungicidal activity than the positive control pyrimethanil on fructose gelatin agar (FGA), and compound III-3 on potato dextrose agar (PDA) indicated high activity compared to the positive control cyprodinil. In vivo greenhouse results indicated that the activity of compounds III-3, III-8, and III-11 was significantly higher than that of the fungicide pyrimethanil. Scanning electron micrography (SEM) and transmission electron micrography (TEM) were applied to illustrate the mechanism of title compounds against B. cinerea. The title compounds, especially those containing a fluorine atom at the ortho-position on the benzene ring, could maintain the antifungal activity against B. cinerea, but their mechanism of action is different from that of cyprodinil. The present study lays a good foundation for us to find more efficient reagents against B. cinerea.